Zwitterionic-anionic surfactant mixture for chemical enhanced oil recovery without alkali. (1st January 2020) - Kurnia, Ivan; Zhang, Guoyin; Han, Xu; Yu, Jianjia
Abstract: Scaling problems and complex produced fluid treatment are amongst the issues attributed to the use of alkali in Daqing chemical enhanced oil recovery (EOR) operations. These problems have incurred additional operating cost due to damage suffered by production/injection wells, surface facilities, and possibly the reservoir. This study presents the formulation of surfactant mixtures for chemical EOR in the absence of alkali by using combination of zwitterionic and anionic surfactants. The zwitterionic-anionic surfactant mixtures were formulated and screened based on aqueous stability, interfacial tension (IFT) measurement, and microemulsion phase behavior. Coreflood experiments were conducted to investigate recovery performance of the selected surfactant pair. Mixture of cocamidopropyl hydroxysultaine and alcohol propoxy sulfate outperformed other mixtures of zwitterionic and anionic surfactants investigated. This binary surfactant mixture appeared as a clear and transparent aqueous solution, achieved ultralow IFT in spinning-drop IFT measurement, and formed substantial middle-phase microemulsion in phase behavior test, indicating a synergistic behavior between the surfactant pair. The ultralow IFT achieved by the binary surfactant mixture led to displacement 63–75% of residual oil in place during coreflood experiments, for which the surfactant retention was around 0.08 mg/g rock. This result shows that zwitterionic-anionic surfactant mixture can provide an alternative approach toward optimizing chemical EOR processes without alkali.